FGF-7 Dictates Osteocyte Cell Processes Through Beta-Catenin Transduction - Liu, Xiao-Yu; Li, Xin; Bai, Ming-Ru; Chen, Xia; Wang, Cheng-Lin; Xie, Jing; Ye, Ling (Scientific reports, 2018)
It is well recognized that osteocytes communicate with each other via gap junctions and that connxin43 (Cx43) shows its great potential in gap junction for the contribution enabling transmission of small molecules and operating in an autocrine/a paracrine manner. Fibroblast growth factors (FGFs) play significant roles in new bone formation and adult bone remodeling, and FGF signaling is regulated by the precise spatiotemporal approaches. However, the influence of FGF7 on osteocyte cell processes is not well elucidated. In this study, we aimed to examine the impact of FGF7 on osteocyte cell processes by characterizing the expression of Cx43 and to reveal the underlying mechanism regulating this cell process. We first found that the mRNA level of FGF7 was higher relative to other FGF family members both in osteocytes cell line (MLO-Y4) and bone tissue. We then demonstrated that FGF7 could increase the expression of Cx43 in osteocytes and promote the cell processes in the form of gap junctions between osteocytes. This modulation was due to the FGF7-induced cytoplasmic accumulation and resultant nuclear translocation of β-catenin. Our results could help us to further understand the importance of FGF7 on bone cell behavior and bone physiology and even pathology.